The power of assessing : guiding powerful practices - Nyberg, Lisa M., 1959-; McGough, Julie V., 1969- (National Science Teachers Association, 2018)
"This book helps teachers understand the power of assessing as a teaching tool by describing different types of assessments (pre-assessments, formative assessments, and summative assessments). It also helps teachers learn how to design authentic assessments to meet the needs of all learners. Finally, it explains how to use metacognition to support instructional decision making"--